2011
DOI: 10.1371/journal.pone.0025335
|View full text |Cite
|
Sign up to set email alerts
|

Aging Negatively Affects Estrogens-Mediated Effects on Nitric Oxide Bioavailability by Shifting ERα/ERβ Balance in Female Mice

Abstract: AimsAging is among the major causes for the lack of cardiovascular protection by estrogen (E2) during postmenopause. Our study aims to determine the mechanisms whereby aging changes E2 effects on nitric oxide (NO) production in a mouse model of accelerated senescence (SAM).Methods and ResultsAlthough we found no differences on NO production in females SAM prone (SAMP, aged) compared to SAM resistant (SAMR, young), by either DAF-2 fluorescence or plasmatic nitrite/nitrate (NO2/NO3), in both cases, E2 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…It is worth mentioning that the stimulation of estrogen synthesis in our OVX animals agreed with the previous studies when the OVX rats were treated with other phytoestrogens. 13,29 Under physiological conditions, the biological effects of estrogen depend not only on the level of estrogen but also on the distribution and expression levels of the corresponding ERs, ERa and ERb, in the target cell [30][31][32] Estrogen and ERs are involved in the physiological function regulation of the female reproductive system. In this study, QBMR significantly up-regulated the expression of ERa and ERb in protein and gene levels in the target tissues, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the stimulation of estrogen synthesis in our OVX animals agreed with the previous studies when the OVX rats were treated with other phytoestrogens. 13,29 Under physiological conditions, the biological effects of estrogen depend not only on the level of estrogen but also on the distribution and expression levels of the corresponding ERs, ERa and ERb, in the target cell [30][31][32] Estrogen and ERs are involved in the physiological function regulation of the female reproductive system. In this study, QBMR significantly up-regulated the expression of ERa and ERb in protein and gene levels in the target tissues, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were then stained with 3,3¢-diaminobenzidine (DAB) (Sigma). 13 The Image-Pro Plus 6.0 System image analysis system was used for quantitative analysis.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, unlike ERβ plays an important neuroprotective role in the central nervous system, in the heart, ERα appears to play a prominent role in most of the other tissues. The critical role of ERa in heart is evidenced by findings from another study showed a increased the ratio of ERβ/ERα in both vascular endothelium and smooth muscle in aged female mice causes the reversal in the antioxidant effect of estrogen to a pro-oxidant profile and is responsible for the increased oxidative stress during aging [112]. In addition, estrogen can reduce ischemia and reperfusion injury and preserve cardiac function via GPR30 and transactivating epidermal growth factor receptors [113].…”
Section: Estrogen and Ers In Age–related Diseasesmentioning
confidence: 99%
“…For example, variation in methylation-associated inactivation of ER gene promoters in various tissue-types, including in the cardiovascular system, has been described in aging rodents and humans. 42,43 The hypermethylation of ERα with aging is more impressive when taken in context of the global hypomethylation of the genome that accompanies the aging process. 44 It is important to mention that the observed changes in ERα expression with aging are cell-type specific since they are not seen in VSMCs and that age-dependent change in ERα expression does not account for the paradoxical effect of E2 on CRP-induced inflammatory mediator expression in VSMCs.…”
Section: Discussionmentioning
confidence: 99%